Optimizing sodium-glucose co-transporter 2 inhibitor use in patients with heart failure with reduced ejection fraction: A collaborative clinical practice statement - Bruce A. Warden; Johannes Steiner; Albert Camacho; Khoa Nguyen; Jonathan Q Purnell; P. Barton Duell; Courtney Craigan; Diane Osborn; Sergio Fazio (Elsevier, 2021)
Heart failure with reduced ejection fraction (HFrEF) is a debilitating disease that is associated with substantial morbidity, mortality, and societal costs. The past three decades have brought about significant advancements in the pharmacologic management of HFrEF, and a corresponding reduction in morbidity and mortality. However, the progress to improve clinical outcomes in real-world settings has stalled in recent years, largely due to underutilization of guideline directed medical therapies (GDMT). The discovery of significant cardio-renal protection from sodium-glucose co-transporter 2 inhibitors (SGLT2i) has ushered in a new treatment paradigm for HFrEF management with SGLT2i therapy becoming an essential component of GDMT. Our Preventive Cardiology and Heart Failure services have established an innovative, multi-disciplinary, collaborative protocol to optimize management of cardiovascular risk factors and facilitation SGLT2i use in patients with HFrEF. The goal of this collaboration is to enhance utilization and safety of SGLT2i for HFrEF management by circumventing medication access issues, the major obstacle to therapy initiation. Within this protocol, our heart failure providers identify patients for the addition of SGLT2i to a background of heart failure GDMT. The patient is then referred to preventive cardiology where the team performs a comprehensive cardiovascular risk assessment, optimizes cardiovascular risk factors, and initiates SGLT2i with an emphasis on medication access, cost minimization, and mitigation of potential side effects. The heart failure team assumes responsibility for modification of heart failure-based therapies, and the preventive team manages diabetes, lipid, and metabolic-based therapies. The patient is followed by both cardiology services in a structured fashion, comparing outcome measures at regular intervals and utilizing our patient registry and bio-repository. This clinical practice statement provides a detailed evidentiary review on the cardiovascular and renal benefits of SGLT2i, outlines the rational for creation of a collaborative protocol, details a structured program that may serve as a template for enhanced heart failure management in other health systems, and addresses challenges encountered and recommendations for use.